Promising Homoeopathic Interventions In The Management Of Kidney Stones: A Narrative Overview - R, Bindu; J, Sundaresan.; Robby, Jabitha V; V, Jayanthdevan; Chandra T , Madhavi; Kumar S, Shandic (Journal of Neonatal Surgery, 2025)
Renal calculus, commonly known as kidney stones, represents a significant health concern due to its prevalence and the discomfort it causes. While conventional treatments, including medications and surgical interventions, are effective, they often come with limitations and potential side effects. This review explores the role of homoeopathy as an alternative and complementary therapy for the management of renal calculus. It provides an overview of the types and causes of kidney stones, discusses the principles and historical development of homoeopathy, and highlights commonly used homoeopathic remedies. The review examines the proposed mechanisms of action of these remedies and compares them to conventional treatments. It synthesizes clinical evidence from trials, studies, and meta-analyses to evaluate the efficacy of homoeopathy in treating renal calculus. The integration of homoeopathic remedies with conventional treatments is considered, along with safety and interaction concerns. The review addresses the challenges and controversies surrounding homoeopathy, particularly in terms of regulatory and ethical issues. Finally, it identifies gaps in current knowledge and suggests directions for future research. This comprehensive review aims to inform healthcare providers and patients about the potential benefits and limitations of homoeopathic approaches to managing renal calculus, ultimately contributing to improved patient care and outcomes.